Perinatal outcomes of adolescent pregnancies: A retrospective study (Annals of Medical Research, 2023)
Aim: Adolescent pregnancies constitute a very important health issue for maternal and fetal with social and economic consequences. The purpose of this study is to analyze the perinatal outcomes of adolescent pregnancies in a training and research hospital.Materials and Methods: Perinatal outcomes for adolescents between the ages of 10 and 19 years old and adults between the ages of 20 and 30 years old between 2015 and 2019 were evaluated and compared retrospectively, using an obstetric and neonatal database from Van Training and Research Hospital.Results: Cesarean section (CS) rates were 19,4 % vs. 30% in the adolescent and control groups, respectively (p
Keywords: Adolescent; Adolescent pregnancies; Live birth; Perinatal outcomes